Een inclusieve geschiedenis van de Gouden Eeuw - Prak, Maarten (TSEG - The Low Countries Journal of Social and Economic History, 2025)
The contribution frames Marjolein ’t Hart’s latest book in the context of her earlier work, which has fundamentally altered our understanding of the Dutch Golden Age through a revision of the effectiveness of the federal state. This is followed by a critical reflection on her latest work, praising its inclusiveness, but casting doubt on the claim that prosperity in the West of the Dutch Republic came at the expense of the populations living in the East.